Programa de calidad de atención para mejorar la satisfacción de los clientes usuarios de tarjeta de crédito del Banco Falabella - Trujillo 2014 - Ramírez Vásquez, Marixa Yanet (2016)
The research called “Service Quality program to improve clients satisfaction of the Falabella bank credit card in Trujillo 2014” demonstrates that this program improves the clients satisfaction of the Falabella Bank credit card in Trujillo 2014. The design used in this research is experimental. It was worked with a sample of 194 clients assisted in the Falabella bank. They took a pre test to measure the client satisfaction of the credit card, it was considered a questionaire of 26 questions with likert questions with answers of total agreement; then, it was applied the quality service program which lasted three months, finishing the program it was applied a post test. Comparing the pre test and the post test of the experimental group, we found that there is a meaningful difference (31%) between the average got by the clients who used the credit card in the pre test with the one got in the post test of the experimental group (P< 0,05), this let us say that the service quality program improves meaningfully the clients satisfaction of the clients who use the Falabella bank credit card in Trujillo City.